Robert S. Duncanson: City and Hinterland - Katz, Wendy J. (Prospects, 2000)
Robert Scott Duncanson, who lived and worked primarily in Cincinnati, Ohio, but also in Michigan, Canada, and Europe, was one of only a few known African-American landscape painters in the 19th century, and one of even fewer to gain a regional, national, and international reputation. His Blue Hole, Flood Waters, Little Miami River (1851) is painted in a style typical of the Hudson River school: a panoramic view of a quiet and apparently pristine wilderness, known then as a popular beauty spot near Cincinnati (Figure 1). The dense forest that encloses the pool, with broken timber around the edges and two drowned branches projecting above the surface of the water, implies isolation and ruggedness. The small, slightly ragged youths fishing in the foreground, though, are more than generic props; they are an image of the desired effect of nature on the often socially mixed residents of the river bottoms, and of Cincinnati in general. The rustic fisherman absorbed and at ease amid a rugged Western landscape loses himself in nature, but instead of making him wild, the experience refines as it acts “But to bind him to his native mountains more.” The image of the two men – as, for example, opposed to figures of genteel tourists – embedded in their native lakes and forests offered reassurance and evidence to local boosters of the positive impact of nature. Nature, in this concept, exerted a softening, soothing influence on those who experienced it, akin to women's moral influence on those within the domestic sphere.
Keywords: Business History and race